The Capital Market and Income Distribution in Yugoslavia: A Theoretical and Empirical Note - Rivera-Batiz, Francisco L. (Quarterly Journal of Economics, 1980)
In a recent article Vanek and Jovicic [1975] (VJ) have analyzed interindustry income differences in Yugoslavia. Their main argument is that in Yugoslavia worker-managed firms accumulate capital and grow mainly by means of their internal (collective) savings. This implies that the income per worker of any firm at any moment of time is composed of a "pure labor income " component and an implicit rental on capital previously accumulated. That is, y = Y/L = a + rK/L, where y is income per worker of any firm, a is the "pure labor income" component, r is the shadow rental on capital, and KIL is capital intensity. They estimate each income component by a cross-sectional re-gression of the form, y = a + bk + u, where y is output per unskilled-labor equivalent, k is capital per un-skilled-labor equivalent, a, b are constants, and u is a random dis-turbance term. The result is, (1) y = 2.50 + 0.0908 k (s.e.) (0.29) (0.040) (t) (8.63) (2.25) R2 = 0.23. A second part of the paper considers factors that could influence the "pure income " component, mainly, inflation rates (Xi), monopoly power (X2), and price controls (X 3). A regression of the residuals from equation (1) on X 1 to X3 is run in order to determine the relative importance of the latter in explaining variation in income per worker among industrial branches. The coefficients obtained are statistically insignificant and the conclusion is that "the variables used do not explain sufficiently the differences in incomes " [VJ, 1975]. Our main criticism is that you cannot try to decompose income per worker variation into a "pure income " and a capital intensity-* E. D. Domar, L. Thurow, and L. Toharia read previous drafts of the manuscript. Errors, of course, remain my sole responsibility.